The efficiency of cell sorting and harvesting methods for in vitro expansion of human umbilical cord blood derived CD34+ hematopoietic stem cells - Borojerdi, Mohadese Hashem; Maqbool, Maryam; Yusoff, Zuraidah; Vidyadaran, Sharmili; Ling, King Hwa; George, Elizabeth; Ramasamy, Rajesh (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
Introduction: During the last three decades hematopoietic stem cell transplantation (HSCT) has become a well-established treatment for many hematologic malignancies. The most important limitation for HSC transplantation is the low number of hematopoietic stem cells (HSC) that can lead to delayed engraftment or graft failures. Numerous attempts have been made to improve in vitro HSC expansion via optimization of various methods such as isolation techniques, supplementing with growth factors, utilizing stromal cells as feeder layer and other culture conditions. Objective: This project is aimed to decipher the efficiency of an isolation technique and retrieval of culture expanded HSC from feeder layer using two different harvesting methods. Materials and Methods: Hematopoietic stem cells from human umbilical cord blood were isolated via MACS mediated CD34+ double sorting. Then, the cells were cultured onto MSC feeder layer for 3 and 5 days. Culture expanded cells were harvested using two different harvesting method namely cell aspiration and trypsinization methods. Hematopoietic stem cell expansion index were calculated based on harvesting methods for each time point. Results: The numbers of HSC isolated from human umbilical cord blood were 1.64 x 106 and 1.20 x106 cells at single and double sortings respectively. Although the number of sorted cells diminished at the second sorting yet the yield of CD34+ purity has increased from 43.73% at single sorting to 81.40% at double sorting. Employing the trypsinization method, the HSC harvested from feeder layer showed a significant increase in expansion index (EI) as compared to the cell aspiration harvesting method (p≤ 0.05). However, the purity of CD34+ HSC was found higher when the cells were harvested using aspiration method (82.43%) as compared to the trypsinization method (74.13%). Conclusion: A pure population of CD34+ HSC can be retrieved when the cells were double sorted using MACS and expanded in culture after being harvested using cell aspiration method.